Syringe service program-based telemedicine linkage to opioid use disorder treatment: protocol for the STAMINA randomized control trial - Dennis P. Watson; James A. Swartz; Lisa Robison-Taylor; Mary Ellen Mackesy-Amiti; Kim Erwin; Nicole Gastala; Antonio D. Jimenez; Monte D. Staton; Sarah Messmer (BMC, 2021)
Abstract Background A key strategy for mitigating the current opioid epidemic is expanded access to medications for treating opioid use disorder (MOUD). However, interventions developed to expand MOUD access have limited ability to engage opioid users at higher levels of overdose risk, such as those who inject opioids. This paper describes the study protocol for testing STAMINA (Syringe Service Telemedicine Access for Medication-assisted Intervention through NAvigation), an intervention that engages high-risk opioid users at community-based syringe service programs (SSP) and quickly links them to MOUD using a telemedicine platform. Methods This randomized control trial will be conducted at three SSP sites in Chicago. All participants will complete an initial assessment with a provider from a Federally Qualified Health Center who can prescribe or refer MOUD services as appropriate. The control arm will receive standard referral to treatment and the intervention arm will receive immediate telemedicine linkage to the provider and (depending on the type of MOUD prescribed) provided transportation to pick up their induction prescription (for buprenorphine or naltrexone) or attend their intake appointment (for methadone). We aim to recruit a total of 273 participants over two years to provide enough power to detect a difference in our primary outcome of MOUD treatment linkage. Secondary outcomes include treatment engagement, treatment retention, and non-MOUD opioid use. Data will be collected using structured interviews and saliva drug tests delivered at baseline, three months, and six months. Fixed and mixed effects generalized linear regression analyses and survival analysis will be conducted to compare the probabilities of a successful treatment linkage between the two arms, days retained in treatment, and post-baseline opioid and other drug use. Discussion If successful, STAMINA's telemedicine approach will significantly reduce the amount of time between SSP clients' initial indication of interest in the medication and treatment initiation. Facilitating this process will likely lead to stronger additional treatment- and recovery-oriented outcomes. This study is also timely given the need for more rigorous testing of telemedicine interventions in light of temporary regulatory changes that have occurred during the COVID-19 pandemic. Trial registration ClinicalTrials.gov (Clinical Trials ID: NCT04575324 and Protocol Number: 1138-0420). Registered 29 September 2020. The study protocol is also registered on the Open Science Framework (DOI 10.17605/OSF.IO/4853 M).